2010
DOI: 10.1111/j.1467-8268.2010.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in Sub‐Saharan African Countries with Consideration to Health and Poverty*

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…A reduction, say, in the survival probability from childhood to adulthood (or, equivalently, an increase in uncertainty about a child's ability to survive to middle age) generates an "insurance effect," which translates into an increase in the number of (or precautionary demand for) children. This is consistent with the evidence provided by Jeon et al (2008), who found that an increase in the infant mortality rate (a proxy for a reduction in the child survival rate) tends to raise the fertility rate in Sub-Saharan Africa.…”
Section: Time Allocation Savings and Life Expectancysupporting
confidence: 92%
“…A reduction, say, in the survival probability from childhood to adulthood (or, equivalently, an increase in uncertainty about a child's ability to survive to middle age) generates an "insurance effect," which translates into an increase in the number of (or precautionary demand for) children. This is consistent with the evidence provided by Jeon et al (2008), who found that an increase in the infant mortality rate (a proxy for a reduction in the child survival rate) tends to raise the fertility rate in Sub-Saharan Africa.…”
Section: Time Allocation Savings and Life Expectancysupporting
confidence: 92%
“…The relationships between family size, maternal health, child health and survival, and household economic welfare have long been a population theme in the demographic and development literature, and recently emphasized by the Millennium Development Goals (UNDP, ). Researchers have pointed to reduced fertility and improvements in adverse reproductive health indicators as most likely to lead to better economic outcomes in African countries (Jeon et al ., ). In Uganda, Ssewanyana and Kasirye () found household welfare status and higher maternal education as key determinants of child health status and inequalities in health.…”
Section: Determinants Of Poverty Transitions: Theoretical and Empiricmentioning
confidence: 97%
“…As mortality rates, and thus uncertainty, fall, the precautionary demand for children also decreases. Jeon et al (2008) and Neanidis (2012) provide evidence that supports this view. That is, they show that a decline in infant mortality (a proxy for higher child survival rate) decreases the fertility rate.…”
Section: Implications Of Changes In Humanitarian Aid For Fertility Tmentioning
confidence: 53%